GRAND MULTIPARITY AND MATERNAL OUTCOME IN ABSENCE OF ADEQUATE ANTENATAL CARE - Khan, Nadia Rashid; Parveen, Saima; Begum, Zareena; Qayyum, Rashida; Malik, Rukhsana (Journal of Postgraduate Medical Institute, 2017)
Objective: To find out the effect of grand multiparity on maternal outcome in absence of adequate antenatal care. Methodology: All un-booked grand multipara with singleton pregnancy at term admitted to Gynae A Unit, Lady Reading Hospital Peshawar were included in the study. Cross sectional study was carried out from 1st June 2012 to 1st Dec 2012. Assessment was done by detailed history, general physical examination, per-abdominal and per-vaginal examination and by obstetrical ultrasound. Mothers were assessed for antenatal and obstetrical complications, mode of delivery and post-partum complications. Results: A total of 50 patients were included in the study. Regarding antenatal complications 6(12%) patients had anemia, 2(4%) had pregnancy induced hypertension, 4(8%) had pre-eclampsia, 2(4%) had eclampsia and 36(72%) didn't had complications. Regarding obstetrical complications 3(6%) patients had placenta previa, 3(6%) had placental abruption, 7(14%) had mal presentation, 3(6%) had obstructed labor and 34(68%) didn't had complications. Regarding post partum complications 5(10%) patients had post partum hemorrhage due to uterine atony, 4(8%) had post partum hemorrhage due to retained placenta, 2(4%) had perineal tears, 3(6%) had subtotal hysterectomy and 36(72%) didn't had complications. Conclusion: In the absence of adequate antenatal care, there was increased likelihood of perinatal complications in grand multiparous women.